A Critical Review on the Design, Manufacturing and Assessment of the Bone Scaffold for Large Bone Defects - Huo, Yi; Lu, Yongtao; Meng, Lingfei; Wu, Jiongyi; Gong, Tingxiang; Zou, Jia’ao; Bosiakov, Sergei; Cheng, Liangliang (Frontiers in Bioengineering and Biotechnology, 2021)
In recent years, bone tissue engineering has emerged as a promising solution for large bone defects. Additionally, the emergence and development of the smart metamaterial, the advanced optimization algorithm, the advanced manufacturing technique, etc. have largely changed the way how the bone scaffold is designed, manufactured and assessed. Therefore, the aim of the present study was to give an up-to-date review on the design, manufacturing and assessment of the bone scaffold for large bone defects. The following parts are thoroughly reviewed: (1) the design of the microstructure of the bone scaffold, (2) the application of the metamaterial in the design of bone scaffold, (3) the optimization of the microstructure of the bone scaffold, (4) the advanced manufacturing of the bone scaffold, (5) the techniques for assessing the performance of bone scaffolds.